Return decomposition over the business cycle - Cenesizoglu, Tolga (Journal of Banking & Finance, 2022)
Based on a generalization of the Campbell and Shiller (1988) approach to a framework with regime-switching parameters and variances, we analyze the conditional variance decomposition of the market return over the business cycle. Discount-rate news is more important than cash-flow news in determining the conditional variance of the market return in recessions, while the opposite holds true in expansions. In an asset pricing model with regime-switching fundamentals, the fact that discount-rate news is more sensitive to changes in investors’ beliefs about the state of the economy, which are more volatile in recessions, provides a potential explanation.